Comfort care of the patient in intensive care - an integrative review - Faria, José Manuel Silva (2018)
Aims - To identify comfort needs and measures of the patient admitted in intensive care units. Material and Method - The investigation questions are: wthat are the comfort needs of the patient admitted in intensive care and which measures should be undertaken to promote comfort to the patient admitted in intensive care units? It was carried out an analysis of the descriptors (keywords) in DeCS and MeSH within the scope of comfort care to elderly patient in intensive care units. Boolean research through data base searching engines: EBSCO, PubMed, B-ON, RCAAP, BVS, Cochrane Library, SciELO. It was obtained a 6488 article population of which 10 articles composed the sample. It was analysed the content of the corpus (corresponding to nursing care) allowing to obtain 2 categories totalizing 55 registration unities. Results - Data distribution was according to theoretical assumptions of Kolcaba Theory: in the category of Comfort Needs (28 registration unities) - 28% are of physical order, 14% environmental, 56% psycho-spiritual and 14% of social order; as far as Comfort Measures are concerned (27 registration unities) - 18% concern suffering relieve, 56% peaceful atmosphere and 26% transcendence. Conclusion - Comfort needs concern essentially physical and psycho-spiritual context and the comfort measures more frequently adopted are aim to relieve suffering and promote a peaceful atmosphere. Nursing disciplin is the one that shows more concern towards comfort care.